China in D. Trump’s Free and Open Indo-Pacific Strategy - Yana Valeryevna Leksyutina (Vestnik RUDN. International Relations, 2019)
With Trump as a president of the US from January 2017 and his decisive actions, which have undermined many agreements reached by previous American administrations (like withdrawal from the TTP, the Paris climate agreement, the Iran nuclear deal, the UNESCO, etc.), the international system and regional subsystems are under serious reconfiguration and readjustments. This accentuates the necessity to systemize Trump’s actions and initiatives in the realm of foreign policy and foreign trade, to interpret these actions’ logic, and to evaluate the changes that Trump’s policies have brought about. It is of high importance to analyze Trump’s strategy in the Indo-Pacific which is the priority region in his foreign policy agenda and the region where two major threats to the US and its allies are coming from - the rise of China as a country that pursues unfair trade and economic policies and reveals assertiveness in securing its core interests, and the threat from the North Korea. The aim of the article is to analyze China’s place in Trump’s Indo-Pacific strategy. By studying American conceptual documents, Trump’s and other American high-level officials’ speeches, the article characterizes Trump’s free and open Indo-Pacific strategy, reveals its commonalities and peculiarities vis-à-vis Obama’s rebalancing to the Asia-Pacific strategy. The article also addresses the issue of Trump’s policies in the region on the economic front, because this is where Trump administration has introduces dramatic changes. Trump’s Indo-Pacific strategy is examined in the article in the context of its impact on the US-China relations. The relations between the two countries - without exaggeration, one of the most consequential for the world - may seriously deteriorate due to not only the evolving US-China trade war, but also contradictions between them over various issues in the IndoPacific region. The article analyzes the aggravation of tensions between the US and China in 2017-2018 over South and East China Seas, Taiwan issue, and North Korea issue.